Sustainable and efficient method utilizing N-acetyl-L-cysteine for complete and enhanced ochratoxin A clearance by antagonistic yeast - Wei, Meilin; Dhanasekaran, Solairaj; Ji, Qihao; Yang, Qiya; Zhang, Hongyin (Journal of hazardous materials, 2023)
With the increasing global climate change, ochratoxin A (OTA) pollution in food and environment has become a serious and potential risk element threatening food safety and human health. Biodegradation of mycotoxin is an eco-friendly and efficient control strategy. Still, research works are warranted to develop low-cost, efficient, and sustainable approaches to enhance the mycotoxin degradation efficiency of microorganisms. In this study, the activities of N-acetyl-L-cysteine (NAC) against OTA toxicity were evidenced, and its positive effects on the OTA degradation efficiency of antagonistic yeast, Cryptococcus podzolicus Y3 were verified. Co-culturing C. podzolicus Y3 with 10 mM NAC improved 100% and 92.6% OTA degradation rate into ochratoxin α (OTα) at 1 d and 2 d. The excellent promotion role of NAC on OTA degradation was observed even at low temperatures and alkaline conditions. C. podzolicus Y3 treated with OTA or OTA+NAC promoted reduced glutathione (GSH) accumulation. GSS and GSR genes were highly expressed after OTA and OTA+NAC treatment, contributing to GSH accumulation. In the early stages of NAC treatment, yeast viability and cell membrane were reduced, but the antioxidant property of NAC prevented lipid peroxidation. Our finding provides a sustainable and efficient new strategy to improve mycotoxin degradation by antagonistic yeasts, which could be applied to mycotoxin clearance. [Display omitted] •NAC treatment enhanced the OTA degradation ability of C. podzolicus Y3 to OTα.•OTA and NAC treatment increased GSH content and changed GSH metabolism.•OTA and NAC treatment altered lipid peroxidation and fatty acid degradation.•NAC reduced yeast’s vitality and damaged membrane at an early stage.•Use of NAC is an efficient and substantial method to eliminate OTA.